Effect of indium substitution on the structure and magnetic characteristics of ternary iron-based nitrides. Issue 8 (1st June 2020) - Wang, W.; Kan, X.C.; Liu, X.S.; Zhang, C.H.; Shezad, M.; Liu, C.C.; Lv, Q.R.; Rehman, K.M. Ur
Abstract: In this paper, the structure and magnetic behaviour of antiperovskite In x Fe4- x N have been investigated systematically. The crystal lattice becomes larger and the Curie temperature decreases with increasing x . The magnetic state changes from a ferromagnetic to a glassy state. In addition, an obvious spin glass (SG) behaviour has been revealed in In0.6 Fe3.4 N ( x = 0.6) with a freezing temperature of T 0 = 73 K, dynamical exponent of zν = 5.51, and flipping time of τ0 = 4.26 × 10 −11 s. The origin of the SG behaviour in In0.6 Fe3.4 N may be attributed to atomic disorders at Wyckoff position 1 a or ferromagnetic frustrations, or the both.